Diseño de un prototipo telemétrico, para lecturas y facturación del servicio de agua potable del Cantón El Empalme - Pallo Velaña, Hevert Mauricio (2015)
This work is composed in part of hardware by a mini computer "Raspberry Pi 2" which is the in charged of storing and processing the information assigned to each module of communication through the internet to the server. This system is composed of solenoid valve and a flow sensor, which sent the data to the computer to be processed and then send them to the slave module (pic 16F887), to be able to be visualized information through the LCD liquid of parallel interface. To wirelessly control was implemented a GSM module 900 sim, for sending text messages to the Subscriber the valve of the monthly consumption of the drinking water service. The Software adapted for the operating system for Raspberry (Pi) is a Raspbian (Debian Linux), within this configuration used the Java programming language, it is the principal for communication, both for the solenoid valve, the flow sensor, which provides us with the sent data and information through the internet, generates reports and sends them to the e-mail address and text messages to mobile devices for each Subscriber, the value of the consumption of the drinking water. This telemetry and control system is found in the author’s house, carried out several tests together with the common meter. In which it took reading and proceeded to create a table of measurements, to compare with the system administrator. In which every minute did the change of reading in m³ which should consist in the application its real consumption report by drinking water service. The present research work provides an alternative to the conventional process, applying the telecommunications-oriented technologies and automation of processes by the use of electronic applications, which offer more accurately plug readings of subscribers by drinking water. For this project as a prototype is said to use hardware and software resources, this being the complement on a physical structure existing in each household water meters.